UMPSA signs collaboration agreements with 3 Institutions in Hebei - Mohamad Ferdaus, Musa (UMPSA, 2023)
BEBEK, 22 September 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has signed memoranda of understanding (MoU) with three TVET institutions in the Hebei Ministry of Education, China. These institutions are Hebei Petroleum University of Technology, Hebei Software Institute, and Shijiazhuang Institute of Railway Technology.